2018
DOI: 10.14196/mjiri.32.55
|View full text |Cite
|
Sign up to set email alerts
|

Burden of esophageal cancer in Iran during 1995-2015: Review of findings from the Global Burden of Disease studies

Abstract: Background: Iran is located in Asian esophageal cancer belt, with age-standardized incidence rate (ASR) of approximately 7 per 100,000 for both men and women. To provide potential solution recommendations for achieving accurate estimations regarding the burden of the disease in Iran, we designed a study to assess the burden of esophageal cancer in Iran during 1995-2015 by collecting data from the Global Burden of Disease studies. Methods: Data were extracted from the Global Burden of Disease (GBD) during 1995… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
(22 reference statements)
1
11
1
Order By: Relevance
“…Contrast, the results of the study suggested that our estimated DALY rates were substantially higher than in many other countries including developing and developed countries [19,21]. For example, the DALY rates per 100 000 people were predicted to about 120 in males and 68 in females in 2015 in Iran, while in the United Kingdom and Japan, it was 88 and 69 in both-sex respectively 2008 [21].…”
Section: Ec Disease Prevalencecontrasting
confidence: 63%
See 1 more Smart Citation
“…Contrast, the results of the study suggested that our estimated DALY rates were substantially higher than in many other countries including developing and developed countries [19,21]. For example, the DALY rates per 100 000 people were predicted to about 120 in males and 68 in females in 2015 in Iran, while in the United Kingdom and Japan, it was 88 and 69 in both-sex respectively 2008 [21].…”
Section: Ec Disease Prevalencecontrasting
confidence: 63%
“…Our study demonstrated that the burden of EC was higher in males. The main reason may be that males were more exposed to risk factors such as tobacco and alcohol consumption [19].…”
Section: Ec Disease Prevalencementioning
confidence: 99%
“…Owing to broad array of data sources and scientific statistical modeling approaches (15,16), GBD study can provide comprehensive estimates of CKD-DM burden to date. GBD 2019 study includes 369 diseases and injuries data in 204 countries and territories (4,10).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining knowledge gap can be filled by a systematic evaluation of available data from the Global Burden of Disease (GBD) database that can provide an opportunity for timely and transparent estimates of disease incidence, mortality, DALY, and other metrics to describe the disease burden at the geographic scales of global, regional, and national levels. So far, a large number of articles using the GBD database have been published and serve to improve health policies (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%